Run to the rainbow - Hillert, Margaret; Corey, Barbara (Cleveland : Modern Curriculum, 1981)
Three children, searching for the rainbow, see many colorful objects.
1.0
K-3
Keywords: Rainbow -- Fiction; Rainbow -- Fiction